PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL ACTIVITY OF JUSTICIA GLAUCA ROTTLER - ARUN JYOTHI BHEEMAGANI,; CHAKRAPANI PULLAGUMMI,; CHANDRA SEKHAR SINGH BHALUDRA,; NIRMALA BABU RAO,; ANUPALLI ROJA RANI, (International Journal of Pharma and Bio Sciences, 2015)
Justicia glauca Rottler, a medicinal plant belongs to dicotyledonous flowering plants family Acanthaceae. Plants from this family have been reported in the scientific literature to possess promising medicinal properties. The preliminary phytochemical analysis and antibacterial activity of Justicia glauca Rottler total plant extracts were carried out using different organic solvents against some pathogenic bacteria viz., Escherichia coli, Klebsiella pneumonia, Bacillus subtilis and Staphylococcus aureus by agar well diffusion method. Results indicated that the petroleum ether, chloroform and ethanol extracts of Justicia glauca Rottler showed significant growth inhibitory activity against Bacillus subtilis, E. coli and Klebsiella pneumonia at 100mg/ml concentration. The most active extracts were compared with the standard antibiotic Ampicillin. The highest zone of inhibition was recorded (13mm) at 100mg/ml concentration of petroleum ether and ethanol Klebsiella pneumonia and Bacillus subtilis respectively. This study revealed that the Justiscia glauca Rottler have a potential broad spectrum antibacterial activity. Combinations of extracts may be the best herbal antibiotics.